Psychiatric Ethics and a Politics of Compassion: The Case of Detained Asylum Seekers in Australia - Zion, D.; Briskman, Linda; Loff, B. (Springer Netherlands, 2011)
Australia has one of the harshest regimes for the processing of asylum seekers, people who have applied for refugee status but are still awaiting an answer. It has received sharp rebuke for its policies from international human rights bodies but continues to exercise its resolve to protect its borders from those seeking protection. One means of doing so is the detention of asylum seekers who arrive in Australia by boat. Health care providers who care for asylum seekers in these conditions experience a conflict of “dual loyalty,” whereby their role in preserving and maintaining the health of patients can run counter to their employment in detention facilities. Many psychiatrists who have worked in the detention setting engage in forms of political activism in order to change the process of seeking refuge.